ELECTIONS IN NIGERIA: A MARCH TO DEMOCRACY OR DE-DEMOCRATIZATION OF THE POLITICAL SPACE? - ODUM, Mbanefo (Socialscientia: Journal of Social Sciences and Humanities, 2021)
Election is undeniably one of the features of democracy that presupposes freedom of citizens to seek political mandate or make choices from among those intending to take up elective political positions. Thus, election stands to lose its democratic flavour and relevance when there are practices that limit the choices of citizens in this regard. The picture of the electoral process in Nigeria has been abysmal. Aside issues relating to outright electoral malpractice, there are certain tendencies being consciously injected into the system, which appear to run contrary to the tenets of democracy. By adopting qualitative method of data collection and analysis based largely on documentary evidence and content analysis, this paper beams searchlight on these noticeable tendencies with a view to establishing whether they are helping in strengthening or eroding the democratic culture. Findings reveal that practices such as rotational political arrangement, consensus candidature, manipulated party primaries, etc destroy rather than strengthen the democratic culture. It is recommended that there is need to expose elections fully to democratic currents instead of adopting anti-democratic measures that appear to shrink the democratic space while serving the primary interests of the political elite.